2007
DOI: 10.1021/ef0700836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Conditions on Gas Quality and Solids Produced by Sewage Sludge Cogasification. 1. Sewage Sludge Mixed with Coal

Abstract: Cogasification of sewage sludge mixed with coal showed that the amount of sewage sludge supplied to the gasifier, depending on its availability, could vary without affecting the gasifier performance; however, it had an influence on the syngas composition. The use of sewage sludge during coal gasification gave rise to an increasing gas yield and energy conversion, mainly because the gas produced had a greater hydrocarbon content. H2S, HCl, and especially NH3 were also found to increase, due to higher contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 23 publications
7
44
1
Order By: Relevance
“…[15][16][17] This is because the sewage sludge usually has high moisture and ash contents, and low heating value, hence the gasification of pure sewage sludge results in the low energy production efficiency. Pinto et al 18 found that the addition of sewage sludge during coal gasification increases the calorific value of the producer gas and fuel conversion. Moreover, they also studied cogasification of sewage sludge with biomass and it was found that the addition of biomass not only increases the production of syngas, but also minimizes the formation of undesirable gases usually generated from sludge gasification.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] This is because the sewage sludge usually has high moisture and ash contents, and low heating value, hence the gasification of pure sewage sludge results in the low energy production efficiency. Pinto et al 18 found that the addition of sewage sludge during coal gasification increases the calorific value of the producer gas and fuel conversion. Moreover, they also studied cogasification of sewage sludge with biomass and it was found that the addition of biomass not only increases the production of syngas, but also minimizes the formation of undesirable gases usually generated from sludge gasification.…”
Section: Introductionmentioning
confidence: 99%
“…Gasification of sewage sludge as well as co-gasification with coal as integrated processes involving primary and secondary reactions have been widely investigated during recent years [11][12][13][14][15][16][17][18]. However, the literature on the reaction of sewage sludge char with an oxidizing agent, which is considered as the most important step in the overall processes process, is very scarce, in contrast to the literature concerning the coal and biomass chars gasification reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto et al [16,17] showed that activated carbon showed a significant role in tar cracking and H 2 production. When activated carbon was applied, the H 2 concentration (including N 2 ) in the producer gas considerably increased to 22 vol%, which was much higher compared to the 5 vol% H 2 concentration obtained without activated carbon.…”
Section: B Methods Of Gasification Of Sludgementioning
confidence: 99%